2017
DOI: 10.1016/j.pmedr.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Pilot survey of a novel incentive to promote healthy behavior among school children and their parents

Abstract: Reversing the obesity epidemic has been a persistent global public health challenge, particularly among low socioeconomic status populations and racial/ethnic minorities. We developed a novel concept of community-based incentives to approach this problem in such communities. Applying this concept, we proposed a school intervention to promote obesity prevention in the U.S. We conducted a pilot survey to explore attitudes towards this future intervention. The survey was collected as a nonprobability sample (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The effectiveness of educational programs on obesity prevention among children implemented in different countries has been demonstrated in many studies [19,[21][22][23], but there were programs with limited success in improving healthy eating behaviours and physical activity among students [24]. Some authors indicate that in the prevention of obesity among children, we need to develop a new concept of a community-based incentive [25]. In the last decade, several obesity prevention programs were also implemented in Poland, some of which were dedicated to the youngest age group [26].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of educational programs on obesity prevention among children implemented in different countries has been demonstrated in many studies [19,[21][22][23], but there were programs with limited success in improving healthy eating behaviours and physical activity among students [24]. Some authors indicate that in the prevention of obesity among children, we need to develop a new concept of a community-based incentive [25]. In the last decade, several obesity prevention programs were also implemented in Poland, some of which were dedicated to the youngest age group [26].…”
Section: Discussionmentioning
confidence: 99%
“…Incentives have been used to encourage participation in school-based interventions including rewards as employed in this study, but also financial incentives (Martin et al, 2014) and donations to charity (Hunter et al, 2015). Previous research has demonstrated good adherence to the intervention when participants have been provided with incentives such as monetary gifts to their school upon meeting intervention goals (e.g., achieving a 2% weight loss goal) (Yoo et al, 2017). Future school-based interventions should therefore consider the use of incentives where possible to enhance compliance to their study aims.…”
Section: Discussionmentioning
confidence: 99%